EL PROCESO DE ENSEÑANZA: APRENDIZAJE CON MÓDULOS AUTOINSTRUCTIVOS - Quiroz, Rosalia (2006)
This paper presents the results of a descriptive, explanatory and correlationalstudy carried out with students offourth cycle ofthe Bibliothecologyand Information Sciences Professional School regarding final grades obtainedin the subject "Law and Deontology in Bibliothecology". Studentswere divided in two groups, the experimental group and the control group.With the first group, we had a personalized teaching experience with the support of an auto-instructive module; with the second, we developed ateaching/leaming process in a traditional way. After several analyses basedthe descriptive statistics, the investigation has demonstrated thatthere are significant differences in the academic produce ofboth groups.We also concluded that the academic achievement of students in the experimentalgroup is not associated to variables as age, sex, job andschool procedence.